Responsibilities of Heirs in Paying Debts of Heirs Perspective Ulama of Regency Bener Meriah - Syifauzzahrah, Syifauzzahrah; Turnip, Ibnu Radwan Siddik (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
One of the heir's responsibilities towards his heirs is to settle the heir's debts that may have existed while he was still alive. The issue is to what extent is the heir's responsibility in paying the heir's debts if the heir does not leave sufficient assets to pay his debts. This paper aims to examine the practices and perspectives of Bener Meriah Regency ulama regarding the responsibility of heirs in paying the heir's debts. This research is empirical legal research, with a legal sociology approach. Primary data sources were obtained from interviews with the public and ulama. Secondary data sources were obtained from primary legal materials, namely the Compilation of Islamic Law and secondary legal materials, namely fiqh books. The data analysis method used is a qualitative analysis method. The results of the research show that some Ulama from Bener Meriah Regency are of the opinion that the heirs have an obligation to pay the debts left by the heir until they are paid off. If the assets left behind are not sufficient, then the heirs will pay them from their own assets, which can be done in installments. However, some ulama agree with the KHI provisions which limit the heir's obligation to pay debts to only the amount of assets left behind, without having to use the heir's assets to pay them as stated in Article 175 paragraph 2. Implementation of the KHI provisions is recommended by means of deliberation with the parties. -the party who owes the debt, so its implementation cannot be forced. Keywords: Heirs, Debt, Heirs, Bener Meriah Regency Ulama